2022
DOI: 10.1039/d2fo00753c
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of chickpea flavonoids on redox imbalance and mitochondrial complex I dysfunction in type 2 diabetic rats

Abstract: CCFE prevented diabetes and its complications via suppressing the up-regulation of the polyol pathway and poly ADP ribose polymerase to alleviate NAD+/NADH redox imbalance, complex I dysfunction and oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…NAD + /NADH redox balance is altered in diabetes; consequently, Fu et al demonstrated that crude chickpea flavonoid extract relieved NAD + /NADH redox imbalance, alleviated mitochondrial complex I dysfunction, and reduced oxidative stress in the pancreas of a T2D rat model [160].…”
Section: Phytochemicals Targeting Dr-an Evidence-based Contribution T...mentioning
confidence: 99%
“…NAD + /NADH redox balance is altered in diabetes; consequently, Fu et al demonstrated that crude chickpea flavonoid extract relieved NAD + /NADH redox imbalance, alleviated mitochondrial complex I dysfunction, and reduced oxidative stress in the pancreas of a T2D rat model [160].…”
Section: Phytochemicals Targeting Dr-an Evidence-based Contribution T...mentioning
confidence: 99%
“…T2DM and AD are two of the most common metabolic diseases and continue to be a leading cause of death worldwide. Evidence is growing for a strong association between mitochondria and T2DM, and mitochondrial dysfunction in peripheral insulin-responsive tissues, such as skeletal muscle, liver, and adipose tissue, is an important initiator of T2DM . For AD, a metabolic hypothesis suggests that the cause of AD might be rooted in mitochondrial dysfunction accompanied by fuel shortage in the brain .…”
Section: Resultsmentioning
confidence: 99%
“…Evidence is growing for a strong association between mitochondria and T2DM, and mitochondrial dysfunction in peripheral insulin-responsive tissues, such as skeletal muscle, liver, and adipose tissue, is an important initiator of T2DM. 14 For AD, a metabolic hypothesis suggests that the cause of AD might be rooted in mitochondrial dysfunction accompanied by fuel shortage in the brain. 10 Reduced ATP levels and glucosestimulated insulin secretion in patients with T2DM are caused by ultrastructural, morphological, and functional abnormalities in the plasma β-cell mitochondria.…”
Section: Effects Of Walnut-derived Peptide Lvrl On Learning and Memor...mentioning
confidence: 99%
See 1 more Smart Citation
“…Isoflavones also presented cancer prevention due to nonhormonal mechanisms, and these compounds suppress angiogenesis, induce apoptosis, and inhibit DNA topoisomerases and cancer cell differentiation (Dulce‐María et al, 2021 ). The NAD + /NADH (nicotinamide adenine dinucleotide) redox imbalance and mitochondrial complex I dysfunction in the pancreas of type 2 diabetes mellitus (T2DM) rats were corrected by chickpea flavonoids (Fu et al, 2022 ). In naturally occurring glycosidic form, isoflavones are conjugated at the 7′ position and are often esterified with acetyl or malonyl groups at the 6′ position of the sugar residue (Taylor et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%